Modulating stem cell differentiation via cell-material interaction - Tijore, Ajay (2016)
Human mesenchymal stem cells (hMSCs) have become the popular candidate in the field of regenerative medicines due to unique properties like multipotency, ease of availability and nonimmunogenicity. In the past, various biochemical methods have been employed to regulate the stem cell differentiation but shortcomings such as tumorigensis and cell death are associated with these methods. Therefore, in recent years, biophysical induction methods are emerging rapidly to control the stem cell lineage commitment. In biophysical induction methods, stem cell behavior can be modulated by regulating the cell-material interactions but detailed study of these cell-material interactions is still limited to date. Here, in the first part, we studied the cell-material interactions by investigating the spatial distribution of integrin-β1 receptors (ITG-β1) at micro- and nanoscale level and systematic study of the relationship between spatial distribution of ITG-β1 and stem cell differentiation (cardiomyogenesis) was performed. We observed the distinct recruitment of ITG-β1 in hMSCs when hMSCs were committed to myocardial lineage induced by cell patterning. We investigated the spatial distribution of ITG-β1 using super resolution imaging in those committed hMSCs. Aligned and elongated ITG-β1 focal adhesions (ITG-β1 FAs) were found in those committed patterned hMSCs in contrast to short and nonaligned ITG-β1 FAs in unpatterned hMSCs. Nanoscale distribution study of integrins revealed that ITG-β1 clusters were uniformly spread within FAs of patterned hMSCs, whereas ITG-β1 clusters were expressed at the periphery of FAs of unpatterned hMSCs. Further, we deciphered the decisive role of cell patterning in generating the optimal cytoskeletal tension in hMSCs to induce cardiomyogenic differentiation via mechanotransduction pathways. The cell’s mechanical properties (cell stiffness and traction forces) which are indicator of cell cytoskeletal tension were drastically reduced in the committed hMSCs as compared to the non-committed unpatterned hMSCs. This fact suggested the positive correlation between the cell patterning-triggered myocardial differentiation and actomyosin-generated optimal cytoskeletal tension within patterned cells. In the next part, we utilized the same dimensions and spatial distribution data of ITG-β1 FAs to design the unique biofunctionalized gold micropatterned platform and reverse engineer the hMSCs differentiation process. The platform was fabricated by following standard photolithography, bioinert polyethylene glycol (PEG) passivation and precise immobilization of ITG-β1 antibodies to gold pattern lanes. Aligned and elongated morphology was shown by hMSCs cultured on this platform and later these patterned hMSCs displayed end to end fusion to form multinucleated myotubes with continuous actin cytoskeleton after two weeks of culture. Aforementioned results illustrated that cell patterning and ITG-β1 mediated signaling synergistically promoted the myotubes formation from patterned hMSCs. This ITG-β1 antibody immobilized micropatterned platform together with hMSCs is a tissue engineered construct and in future, may find use for a wide range of applications, right from muscle tissue engineering to the investigation of stem cell-material interactions to gain insights into signaling pathways involved in stem cell myogenesis.